The effect of mere measurement from a cardiovascular examination program on physical activity and sedentary time in an adult population - Lisa Voigt; Sophie Baumann; Antje Ullrich; Franziska Weymar; Ulrich John; Sabina Ulbricht (BMC, 2018)
Abstract Background Measuring physical activity (PA) and sedentary time (ST) by self-report or device as well as assessing related health factors may alter those behaviors. Thus, in intervention trials assessments may bias intervention effects. The aim of our study was to examine whether leisure-time PA, transport-related PA, and overall ST measured via self-report vary after assessments and whether a brief tailored letter intervention has an additional effect. Methods Among a sample of subjects with no history of myocardial infarction, stroke, or vascular intervention, a number of 175 individuals participated in a study comprising multiple repeated assessments. Of those, 153 were analyzed (mean age 54.5 years, standard deviation = 6.2; 64% women). At baseline, participants attended a cardiovascular examination (standardized measurement of blood pressure and waist circumference, blood sample taking) and wore an accelerometer for seven days. At baseline and after 1, 6, and 12 months, participants completed the International Physical Activity Questionnaire. A random subsample received a tailored counseling letter intervention at month 1, 3, and 4. Changes in PA and ST from baseline to 12-month follow-up were analyzed using random-effects modelling. Results From baseline to 1-month assessment, leisure-time PA did not change (Incidence rate ratio = 1.13, p = .432), transport-related PA increased (Incidence rate ratio = 1.45, p = .023), and overall ST tended to decrease (b = − 1.96, p = .060). Further, overall ST decreased from month 6 to month 12 (b = − 0.52, p = .037). Time trends of the intervention group did not differ significantly from those of the assessment-only group. Conclusions Results suggest an effect of measurements on PA and ST. Data of random-effects modelling results revealed an increase of transport-related PA after baseline to 1-month assessment. Decreases in overall ST may result from repeated assessments. A brief tailored letter intervention seemed to have no additional effect. Thus, measurement effects should be considered when planning intervention studies and interpreting intervention effects. Trial registration ClinicalTrials.gov NCT02990039 . Registered 7 December 2016. Retrospectively registered.